2018
DOI: 10.1111/jmcb.12501
|View full text |Cite
|
Sign up to set email alerts
|

Hot Money and Quantitative Easing: The Spillover Effects of U.S. Monetary Policy on the Chinese Economy

Abstract: We develop a factor‐augmented vector autoregression (FA‐VAR) model to estimate the effects that unanticipated changes in U.S. monetary policy and economic policy uncertainty have on the Chinese housing, equity, and loan markets. We find the decline in the U.S. policy rate since the Great Recession has led to a significant increase in Chinese housing investment. One possible reason for this effect is the substantial increase in the inflow of “hot money” into China. The responses of Chinese variables to U.S. sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
(71 reference statements)
3
20
0
Order By: Relevance
“…The reversed effect of hot money shocks and the negative impact of positive price shocks on the national factor result from the monetary tightening induced by these shocks. Our last finding is also consistent with that of Ho et al (2018), who investigate the spillover effect of the U.S. monetary policy and find that hot money can be the valid channel through which U.S. monetary policy could affect Chinese real estate market.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reversed effect of hot money shocks and the negative impact of positive price shocks on the national factor result from the monetary tightening induced by these shocks. Our last finding is also consistent with that of Ho et al (2018), who investigate the spillover effect of the U.S. monetary policy and find that hot money can be the valid channel through which U.S. monetary policy could affect Chinese real estate market.…”
Section: Introductionsupporting
confidence: 90%
“…Other studies also find this phenomenon. For instance,Ho et al (2018) find that the responses of the Chinese economy to U.S. monetary policy shocks and policy uncertainty shocks exhibit different dynamics in periods before and after the federal funds target rate hit the ZLB in the United States, which suggests the existence of structural changes both in the Chinese economy and in the transmission mechanism of U.S. monetary policy.…”
mentioning
confidence: 99%
“…in the U.S.A. and economic policies in China. It is evident that exchange and interest rates of emerging economies are directly affected by the monetary policy of U.S.A. (Ho, Zhang, & Zhou, 2018). The uncertainty in interest rate (E.P.U.)…”
Section: Marketisation Impact Epu and Dividend Sustainabilitymentioning
confidence: 99%
“…Therefore, the monetary policy tools of the Fed shifted between "conventional" and "unconventional", they were restricted by the effectiveness of expectations of economic subjects on new policies, thereby significantly increasing the US monetary policy uncertainty (MPU) (Husted et al, 2020). Previous studies have shown that the US MPU generates a spillover effect on the economic activities and financial markets in China and other countries through exchange rates, interest rates, trade, capital flow, and other channels (Baker et al, 2016;Ho et al, 2018;Jiang et al, 2019a). With the continuously accelerated global financial integration progress and gradual opening of transaction channels such as "Shanghai-London Stock Connect" and "Shanghai-Hong Kong Stock Connect", the cross-border financial risk shock faced by China is increasingly aggravated.…”
Section: Introductionmentioning
confidence: 99%